2013
DOI: 10.1179/0371955313z.00000000069
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrochemical conversion of metal oxides to metal by molten salt electrolysis: a review

Abstract: Little over a decade ago, Professor Derek Fray's group at the University of Cambridge, UK, discovered that a solid metal oxide can be directly reduced to metal by cathodically polarising it in a molten salt electrolytic cell. The simple electrochemical process attracted worldwide attention and significant efforts have been made since then to study and develop the process for production of many metals/alloys from their oxides. The process, with necessary modifications, is being studied and adapted as a head-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 103 publications
(208 reference statements)
0
62
0
Order By: Relevance
“…A solid metal part will be in close physical contact with the oxide preform through which the electrons from an external DC power source will be supplied to it. The thermodynamic stability and electrical characteristics of an oxide electrode are known to have strong influence on its electro-reduction behaviour [3,5,6] in addition to many other parameters such as applied voltage, duration of electrolysis, sintering temperature of the oxide performs etc. [3,7,8] .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A solid metal part will be in close physical contact with the oxide preform through which the electrons from an external DC power source will be supplied to it. The thermodynamic stability and electrical characteristics of an oxide electrode are known to have strong influence on its electro-reduction behaviour [3,5,6] in addition to many other parameters such as applied voltage, duration of electrolysis, sintering temperature of the oxide performs etc. [3,7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamic stability and electrical characteristics of an oxide electrode are known to have strong influence on its electro-reduction behaviour [3,5,6] in addition to many other parameters such as applied voltage, duration of electrolysis, sintering temperature of the oxide performs etc. [3,7,8] . Several studies have been reported on the electrochemical reduction of oxides such as TiO 2 [1,3,5,[8][9][10][11] , Nb 2 O 5 [7,12,13] , UO 2 [14][15][16] , SiO 2 [17][18][19][20][21][22][23][24][25][26] etc.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations